PENGARUH HUBUNGAN EKSEKUTIF DAN LEGISLATIF, LATAR BELAKANG PENDIDIKAN, DIVIDED GOVERNMENT DAN DANA ALOKASI UMUM TERHADAP KETERLAMBATAN PENETAPAN APBD DI KABUPATEN LIMAPULUH KOTA - Elmita Sari; Emrinaldi Nur DP; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was intended to study effect of executive and legislator association, education background, divided government and general allocation fund (DAU) on the Regional Budget Delay. This research used 75 as a sample which legislators consisting of budget board, local governmental budget team (TAPD) and regional working unit (SKPD), the results of the General Election for the Legislatives 2009 and the Direct Elections of District Head of the Year 2010 in Limapuluh Kota regency. The data of this research was collecting by questionnaire which analized by using logistic regression. The result of this research show that executive and legislator association and educational background influence the Regional Budget Delay. While divided government and General Allocation Fund (DAU) does not influence the Regional Budget Delay.Keywords: executive, legislator, association, education, and regional budget delay